Microbiological studies on Rhizobium leguminosarum isolated from pea (Pisum sativum L.) - Shahzad, Farood; Taj, Muhammad Kamran; Abbas, Ferhat; Shafee, Muhammad; Essote, Safed Ahmed; Taj, Imran; Achakzai, Abdul Manan (Bangladesh Journal of Botany, 2019)
Rhizobia are the true bacteria that establish symbiotic relationship leading to the development of new root nodules. This study has been designed to evaluate the microbiological aspects of Rhizobium leguminosarum in target area. A total of 1000 (200 from each site) roots were collected from five different agriculture fields (Quetta, Pishin, Killa Abdulla, Kuchlak and Hanna Urak) and screened through different standard microbiological procedures. Results revealed that 665/1000 (66.5%) roots samples were positive for Rhizobium leguminosarum. The highest percentage was from Pishin 180/200 (18%) and Killa Abdullah 160/200 (16%). A remarkable growth of Rhizobium leguminosarum was noted at 28 to 30°C whereas, less growth was recorded at 24, 34 and 42°C. Similarly, Rhizobium leguminosarum showed growth at pH 5 to 10, but superlative pH values for the growth of Rhizobium leguminosarum were from 6 to 8 pH. The PCR reconfirmed 1300 bp band of 16S rRNA gene of Rhizobium leguminosarum. The organism was further applied as biofertilizer and showed promising results in subjected plants. Medicinal plants application showed that Rhizobium leguminosarum was sensitive to different plants. However, the effects of insecticides showed that Cypermethrin exhibited least zone of inhibition 10 and 11 mm, while Chlorpyrifos showed least zone of inhibition 14 and 17 mm by using disc and well method with (1: 16) dilution. These findings ensure the devastation of microbiota in rhizosphere with rational use of these pesticides that may result in adverse effects over crop productions in the region.